(3GdeTcdGJ GdYedjI aj LQGFe GdTjc (B/s - (3gQLI, eUWai eLOjs ((3GdEScfOQjI(B: s (3OGQ eMehO ddfTQ hGdJhRjY(B, s, 2005)
(3JYQja GdTjc hCfhGYg hGdJaQbI Hjfg Hjf GdChQGb GdJLGQjI GdCNQi(B- (3GdTQhW GdTcdjI hGdehVhYjI ddTjc(B- (3CQcGf GdLQjeI(B- (3CSHGH GdEHGMI aj GdEeJfGY Yf UQa GdTjc(B- (3fXQ GdOYhi hGdMce ajgG(B.s
(3GdeQGLY U(B. 295s
Keywords: (3GdLQjeI hGdeLQehf(B- (3GdTjcGJ (B- (3eUQs; (3GdTjcGJ(B- (3bhGfjf hJTQjYGJ(B- (3eUQs; (3LQGFe GdCehGds